Mapping Evidence on Engklek and Social-Emotional Development in Early Childhood: A Systematic Literature Review - Nurhayati Nurhayati; Sri Maisari; Mohamad Fauzil Adhim Asnawi; Hamimah Hamimah; Hennira Rohyatin (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Social-emotional development is a core dimension of early childhood education because it shapes children’s ability to build relationships, manage emotions, and adapt to social environments. A growing body of research indicates that traditional games can foster these competencies through activities that require cooperation, interpersonal communication, and self-regulation. This article presents a systematic literature review to map and synthesize empirical evidence on the contribution of the traditional game engklek to young children’s social–emotional development. The literature search was conducted across Google Scholar, Garuda, DOAJ, ERIC, and institutional repositories, covering publications from 2015 to 2025. Study selection followed the stages of identification, screening, and eligibility assessment, resulting in 14 articles that met the inclusion criteria and were thematically analyzed. The synthesis indicates that engklek contributes to three main domains: (1) social skills (e.g., cooperation, rule-following, and communication), (2) emotion regulation (e.g., frustration control and persistence), and (3) prosocial behavior and peer interaction quality (e.g., empathy, sharing, and conflict resolution). These findings suggest that engklek functions not only as a cultural practice but also as a pedagogical medium that aligns with play-based learning grounded in local contexts. The review supports integrating traditional games into early childhood curricula and developing contextual, inclusive, and child-friendly instructional strategies.